Perencanaan Strategis SI/TI Menggunakan Metode Ward And Peppard di SMKN 1 Tanjung Selor - Elma Christin; Johan Tambotoh (STMIK Budi Darma, 2022)
Ward and Peppard is a computer-based application portfolio identification process that will support the organization in implementing its business plan and realizing its business goals. SMK Negeri 1 Tanjung Selor is an educational institution located in North Kalimantan. SMK Negeri 1 Tanjung Selor has become an educational institution that is developing rapidly, but has not implemented information systems and information technology properly so that existing operational services are less than optimal, and it is necessary to make strategic planning that can support school business plans and development, The form of strategic planning that will be discussed in this study uses the Ward and Peppard method with pest analysis method tools, SWOT, Value Chain, and Mcfarlan Strategic Grid analysis methods. The results of the analysis of this study solve the existing problems with several proposed information systems that can help the school's work for the better